judul artikel: judul artikel - Haikal, Fadel Muhammad; Rizal, Bayu Thomi (Universitas Hamzanwadi, 2025)
This study aims to analyze the effect of the baseball game on increasing students' interpersonal intelligence. The research method uses quantitative with quasi experimental design. The population in this study was 52 students using total sampling technique. Data collection is done through a questionnaire with statements about interpersonal intelligence. While the data analysis technique uses Kolmogorov-Smirnov, the normality test results show the sig value of the experimental class 0.200 greater than 0.05 and the control class 0.054 greater than 0.05 so that the data is normally distributed. The results showed a significance value of 0.000 smaller than 0.05, so it can be concluded that there is a significant difference in the scores of experimental and control class students after treatment. the results of students' interpersonal intelligence on the prosttest results in the control class fell into the low category as many as 3 students (11%) and in the medium category as many as 23 students (89%). While the categorization of the results of students' interpersonal intelligence in the experimental class after the treatment of the baseball game in the medium category was 4 students (14%) and the high category was 22 students (86%). From this it can be concluded that the baseball game on interpersonal intelligence is effective in grade VI students of Teladan Suci Islamic Elementary School.